2022
DOI: 10.5194/wcd-3-1037-2022
|View full text |Cite
|
Sign up to set email alerts
|

Meridional-energy-transport extremes and the general circulation of Northern Hemisphere mid-latitudes: dominant weather regimes and preferred zonal wavenumbers

Abstract: Abstract. The extratropical meridional energy transport in the atmosphere is fundamentally intermittent in nature, having extremes large enough to affect the net seasonal transport. Here, we investigate how these extreme transports are associated with the dynamics of the atmosphere at multiple spatial scales, from planetary to synoptic. We use the ERA5 reanalysis data to perform a wavenumber decomposition of meridional energy transport in the Northern Hemisphere mid-latitudes during winter and summer. We then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Earlier in (Sukhanovskii et al, 2023) it was shown that the atmospheric regime, in which the mean flow and baroclinic waves are similar to those in the real atmosphere, i.e. strongly non-stationary waves with main modes m = 2−8 (see mode decomposition analysis in (Lembo et al, 2019(Lembo et al, , 2022)), can be realized only in a short interval of the main parameters. We have chosen this regime to study Arctic warming using laboratory and numerical modeling.…”
Section: Flow Structurementioning
confidence: 99%
“…Earlier in (Sukhanovskii et al, 2023) it was shown that the atmospheric regime, in which the mean flow and baroclinic waves are similar to those in the real atmosphere, i.e. strongly non-stationary waves with main modes m = 2−8 (see mode decomposition analysis in (Lembo et al, 2019(Lembo et al, , 2022)), can be realized only in a short interval of the main parameters. We have chosen this regime to study Arctic warming using laboratory and numerical modeling.…”
Section: Flow Structurementioning
confidence: 99%
“…Earlier in it was shown that the atmospheric regime, in which the mean flow and baroclinic waves are similar to those in the real atmosphere, i.e., strongly non-stationary waves with main modes of m = 2 − 8 (see mode decomposition analysis in Lembo et al, 2019Lembo et al, , 2022, can be realized only in a short interval of the main parameters. We have chosen this regime to study Arc-tic warming using laboratory and numerical modeling.…”
Section: Flow Structurementioning
confidence: 99%
“…Recurrent and/or quasi‐stationary large‐scale circulation patterns, typically referred to as weather regimes, have been identified in a number of regions across the globe. These include the Euro‐Atlantic sector (Michelangeli et al., 1995; Vautard, 1990), the Eastern Mediterranean (Alpert et al., 2004; Hochman et al., 2019), East Asia (Yang et al., 2022), Oceania (Kidson, 2000), the Pacific (Fabiano et al., 2021; Michelangeli et al., 1995), the full Northern Hemisphere (Lembo et al., 2022) and North America (Straus et al., 2007; Vigaud et al., 2018).…”
Section: Introductionmentioning
confidence: 99%